Investigating inclusive pedagogy in foundation phase rural ordinary classrooms in Malamulele (Vhembe district, Limpopo province) - Mabasa - Manganyi, Rachel Basani (My University, 2018)
It is a well established case that teachers’ use of pedagogical practices have diverse impact on the learner participation, access and achievement. The purpose of the study was to investigate inclusive pedagogical practices employed by four foundation phase teachers in teaching Xitsonga Home Language and teaching Mathematics in Xitsonga. This study therefore reports on the teachers’ use of Inclusive pedagogical practices through direct observations and individual interviews. While there are numerous studies that have explored the use of inclusive pedagogy from an urban context, this study focused on investigating the extent to which inclusive pedagogy is evident in foundation phase rural ordinary classrooms, grade one to three. Vygotsky’s theory of social constructivism formed the basis of the theoretical framework that underpins pedagogy. I argue that the social constructivist model holds the promise of inclusive pedagogy from which follows inclusive classroom practices. The study used the framework for participation in classrooms created by Florian (2014) to provide an analytical approach to examine inclusive pedagogical practices where I specifically used the four elements and questions which Florian and Black-Hawkins (2011) proposed as relevant in order to identify and understand employed inclusive pedagogy by teachers in ordinary classrooms. The findings are that, out of the ten inclusive pedagogical practices identified by the literature, seven of them were found to be employed by four foundation phase teachers in rural ordinary classrooms
Submitted in partial fulfillment of the degree of Master of Education in the Faculty of Humanities at the Wits School of Education, studies in Education, University of the Witwatersrand, Johannesburg, October, 2018